Shape memory ceramic and manufacturing and 4D printing method thereof
By mixing liquid silicone with ceramic filler and using 4D ASM technology, combining UV/ozone treatment and pyrolysis treatment, SiOC-based SMC with multi-modal shape memory capabilities was developed, solving the manufacturing problem of complex curved structural ceramics and realizing the Efficient and precise shape control.
Patent Information
- Application Number
- CN202480002782.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-21
- Filing Date
- 2024-06-21
- Publication Date
- 2025-02-21
AI Technical Summary
Manufacturing shape memory ceramics (SMCs) with complex curved structures faces great challenges, including complex processing techniques and the brittleness of ceramic materials, making it difficult to achieve precise control of the shape memory properties of ceramics.
By physically mixing liquid silicone with different ceramic fillers, SiOC-based SMC was developed and four-dimensional (4D) additive-reduction composite manufacturing technology (4D ASM) was used, combining UV/ozone treatment and pyrolysis treatment to achieve multi-ceramics Pattern shape memory ability.
The initial/reverse and overall/local multimodal shape memory capabilities of ceramics are realized, geometric flexibility is enhanced, and shape modification can be made through heterogeneity of thermal expansion-heat shrinkage behavior, solving the efficiency and stability of traditional SMC manufacturing methods. Sexual limitations.
Smart Images

Figure CN119497665A_ABST
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to U.S. Provisional Patent Application No. 63 / 509,284 filed on June 21, 2023, which is incorporated herein by reference in its entirety. Technical Field
[0002] The present invention generally relates to shape memory ceramics (SMC) and manufacturing techniques thereof. More specifically, the present invention relates to shape memory ceramics made by four-dimensional (4D) additive and subtractive composite manufacturing techniques. Background Art
[0003] Unlike shape memory alloys (SMA), shape memory ceramics (SMC) are a class of materials that have the unique ability to recover their original shape after being deformed when subjected to certain stimuli, such as temperature changes. These ceramics exhibit shape memory effects due to their ability to undergo reversible phase transitions between different crystal structures. Unlike the more commonly known SMAs, SMCs offer advantages such as high temperature stability, corrosion resistance, and biocompatibility. These materials have significant application prospects in aerospace, biomedical devices, actuators, and adaptive structures, where precise shape control and reliable performance are critical. However, the manufacture of SMCs with complex curved structures has encountered great challenges due to the complex processing techniques required and the inherent brittleness of ceramic materials. Achieving precise control of the shape memory properties of ceramics, especially in curved geometries, remains a major obstacle to the development and widespread adoption of these materials.
[0004] There is a wave of research going on in the additive manufacturing (AM) community for building structural materials. Currently, three-dimensional (3D) printing systems, as a type of AM system, are fast and can produce large structures, but there are still potential difficulties. They usually have to sacrifice accuracy for speed or scale. Fortunately, a solution is beginning to emerge: combining AM with subtractive manufacturing (SM) to create additive and subtractive manufacturing (ASM). This concept can bring revolution to 3D printing by providing fast, accurate and large-scale technology.
[0005] However, the high melting points of some materials have hindered the progress of 3D printing. Fortunately, inspiration from origami and kirigami techniques has promoted the progress of four-dimensional (4D) printing.
[0006] 4D printing is an emerging technology that adds an additional time dimension to traditional 3D printing by enabling materials to change their shape or properties over time in response to external stimuli. This innovative approach has great potential to create dynamic and adaptive structures that can self-assemble, self-repair, or change shape on demand. 4D printing typically involves the use of smart materials, such as shape memory polymers or hydrogels, which can be programmed to respond to stimuli such as heat, light, or moisture. Although still in its early stages, 4D printing has demonstrated applications in fields such as architecture, robotics, medicine, and aerospace, providing solutions to complex manufacturing challenges and enabling new functionality that was previously unattainable.
[0007] Combining SMC with 4D printing technology offers exciting opportunities for developing advanced materials and structures with dynamic shape-changing capabilities and high-temperature elasticity. However, there are significant barriers to large-scale production of SMCs with complex curved structures. Traditional manufacturing methods (such as sintering or hot pressing) are often limited in their efficiency and stability in preparing complex shapes. Additive manufacturing technologies, including 3D printing, offer potential solutions to overcome these challenges by enabling precise control over material deposition and layer-by-layer construction. However, scaling up production to meet commercial demand while ensuring quality control and cost-effectiveness remains a key challenge that must be addressed to unlock the full potential of SMCs in a variety of applications. Summary of the invention
[0008] The present invention solves the aforementioned shortcomings and provides significant improvements to conventional SMCs and their manufacturing methods, and the successful attempts of the initial / reverse and global / local multi-mode shape memory behaviors of ceramics pave the way for various types of self-deformation of SMCs.
[0009] The present invention may involve a martensitic phase transformation, providing a novel mechanism for SMC. Various embodiments of the present invention provide SMCs with heterogeneity in thermal expansion-contraction behavior. In some embodiments of the present invention, a universal SiOC-based SMC is developed in a convenient manner by physically mixing liquid silicone with different ceramic fillers. 4D ASM can greatly enhance geometric flexibility.
[0010] In addition, the present invention expands the size of the SMC structure from the micro / mesoscopic to the macroscopic scale and realizes the initial / reverse and global / local multi-mode shape memory capabilities of ceramics.
[0011] According to a first aspect of the present invention, a SMC is provided. The SMC comprises a first portion and a second portion. The first portion and the second portion of the SMC are bonded. The SMC is an elastomer-derived ceramic comprising silicon oxycarbide. The first portion of the SMC is treated with ultraviolet ozone (UV / ozone), and the second portion of the SMC is not treated with UV / ozone.
[0012] According to one embodiment of the present invention, the second portion of the SMC has a plurality of grooves.
[0013] According to another embodiment of the present invention, the first portion of the SMC forms a plurality of strips on the surface of the second portion of the SMC.
[0014] According to a second aspect of the present invention, a method for manufacturing a SMC is provided, comprising: providing a precursor structure comprising polydimethylsiloxane (PDMS); treating a portion of a surface of the precursor structure with UV / ozone; and treating the precursor structure using pyrolysis to generate the SMC.
[0015] According to one embodiment, the step of providing a precursor structure includes: forming a first precursor using additive manufacturing; and cutting or engraving the first precursor using a laser to form the precursor structure.
[0016] According to another embodiment, the additive manufacturing includes doctor blade coating or ink direct writing printing.
[0017] The step of treating with UV / ozone includes: masking a surface of the precursor structure with laser cut paper; and treating the masked surface with UV / ozone.
[0018] According to one embodiment, after the pyrolysis process, the manufacturing method further includes: heating the SMC in air.
[0019] According to another embodiment, after the pyrolysis process, the manufacturing method further includes: heating a portion of the SMC in air.
[0020] According to yet another embodiment, after the pyrolysis process, the manufacturing method further includes: heating at least a portion of the SMC in air using induction heating.
[0021] According to various embodiments of the present invention, the above steps are performed in a turntable system having multiple stations.
[0022] According to various embodiments of the present invention, the precursor structure further includes ceramic particles (filler) or glass particles (filler).
[0023] In some embodiments of the present invention, the SMC has portions treated with UV / ozone, and different portions of the SMC may have different material properties including thermal expansion and thermal contraction for efficient use in 4D printing.
[0024] The present invention introduces a completely new manufacturing mechanism for silicone matrix composites, namely, utilizing the heterogeneity of thermal expansion-contraction behavior. Based on the newly developed SMC manufacturing mechanism (heterogeneity of thermal expansion-contraction behavior), a universal SiOC-based SMC can be developed in a convenient way by physically mixing liquid silicone with different ceramic fillers.
[0025] In some embodiments of the present invention, compared with the ceramic powder pressing method used in previous studies, the geometric flexibility is significantly enhanced by 4DASM, i.e., 2D / 3D printing combined with laser engraving / cutting of ceramic precursors. In addition, the size of the SMC structure is expanded from micro / mesoscopic to macroscopic scale, thereby achieving both initial / reverse and global / local multi-mode shape memory capabilities of the ceramic. The advances distinguish the present invention from existing research on SMC. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Embodiments of the present invention are described in more detail below with reference to the accompanying drawings, in which:
[0027] Figure 1 is a schematic diagram of a precursor structure having a plurality of grooves and constructed from an elastomeric material including PDMS via additive manufacturing or subtractive manufacturing according to one embodiment of the present invention;
[0028] Figure 2 is another schematic diagram of a precursor structure according to this embodiment, wherein a portion of the precursor structure is treated with UV / ozone;
[0029] Figure 3 is a schematic diagram of SMC treated with pyrolysis according to this embodiment;
[0030] Figure 4 is a schematic diagram of a precursor structure using a mask according to another embodiment of the present invention;
[0031] Figure 5 is another schematic diagram of a precursor structure according to this embodiment, wherein a portion of the precursor structure is treated with UV / ozone;
[0032] Figure 6 is a schematic diagram of SMC treated with pyrolysis according to this embodiment;
[0033] Figure 7 is a diagram of a 4D ASM of a heterogeneous precursor engineering and SMC according to an embodiment of the present invention;
[0034] Figure 8 is a schematic diagram of a plurality of precursor structures with a groove depth of 100-500 microns for 4D printing according to this embodiment;
[0035] Fig. 9Demonstrate the use of Figure 7 The method shown generates a series of images of shape and material changes during heat treatment of a ceramic precursor structure;
[0036] Fig.10 Show thermal expansion Fig. 9 Finite element method (FEA) simulation results showing the effect of bending deformation on the ceramic precursor structure;
[0037] Fig.11A , 11B and 11C is derived from Fig. 9 Scanning electron microscope (SEM) image of the first generation elastomer-derived ceramic (EDC) of the precursor subjected to induction heat treatment at 1,300°C is shown;
[0038] Fig. 12A and 12B is a graph showing the porosity of the first generation EDC;
[0039] Fig.13 A series of images depicting shape and material changes during heat treatment of a first generation EDC derived from a precursor structure having grooves with a depth of 200 microns, thereby producing a second generation EDC, according to an embodiment of the present invention;
[0040] Fig.14 A series of images depicting shape and material changes during heat treatment of a first generation EDC derived from a precursor structure having grooves with a depth of 500 microns, thereby producing a second generation EDC, according to an embodiment of the present invention;
[0041] Fig.15 A series of images depicting shape and material changes during heat treatment of a first generation EDC derived from a precursor structure having grooves with a depth of 100 microns, thereby producing a second generation EDC, according to an embodiment of the present invention;
[0042] Fig.16 is a graph showing the effect of precursor groove depth on the curvature of the resulting first and second generation EDCs with reverse shape memory capability;
[0043] Fig.17 is a graph showing the X-ray diffraction analysis of the first and second generation EDCs;
[0044] Fig.18 A diagram depicting a method of making a second generation EDC or a first generation / second generation composite EDC according to one embodiment of the present invention;
[0045] Fig.19An illustration depicting 3D printing and localized surface treatments providing the potential for enhanced geometric complexity in 3D construction and 4D deformation according to one embodiment of the present invention;
[0046] Fig. 20 A further illustration depicting 3D printing and localized surface treatment in an exemplary application of the present invention, featuring a 4D printed first generation EDC produced from a heterostructure precursor generated according to an embodiment of the present invention;
[0047] Fig.21 is a series of images of shape and material changes during heat treatment of a heterogeneous precursor in an exemplary application;
[0048] Fig.22A showing a 3D scanned image of a 4D printed all-ceramic blisk in another exemplary application of the present invention; and Fig. 22B Showing color mapping analysis of a 3D scanned image of a 4D printed all-ceramic blisk;
[0049] Fig.23A and 23B The PDMS / 20wt% ZrO in the precursor of some embodiments of the present invention is shown in the experiment. 2 Mechanical and thermal characterization of Fig.23A Demonstrating tensile behavior, with the inset showing the 0%-10% strain region during loading used to obtain the corresponding Young's modulus; and Fig. 23B PDMS / 20wt% ZrO 2 Thermal expansion behavior at temperatures below 445°C;
[0050] Fig.24A and 24B Show as Fig. 20 Thickness and Young's modulus of the UV / ozone film on the heterostructure precursor shown; where Fig.24A Display SEM images; and Fig. 24B Demonstrate nanoindentation testing;
[0051] Fig.25 Show as Fig.21 FEA simulation results of the thermal expansion process of the heterostructure precursor shown;
[0052] Fig.26 Demonstrating a second generation EDC resulting from a first generation EDC of a 4D printed all-ceramic blisk in an exemplary application of the present invention;
[0053] Fig.27A and 27BTwo series of images showing the shape and material changes of a first-generation EDC derived from a 4D-printed all-ceramic blisk heterostructure precursor under heat treatment, resulting in a second-generation EDC;
[0054] Fig.28 A diagram depicting doctor blade coating and laser processing according to an embodiment of the present invention, thereby providing the potential for increased manufacturing speed and accuracy;
[0055] Fig.29 A diagram depicting the batch production capability of heterogeneous precursor materials aided by a multi-station turret system in one embodiment of the present invention;
[0056] Fig.30 Describe the use Fig.28 Illustration of the large-scale production of a 10×10 array of ceramic kirigami structures generated by doctor blade coating and laser processing, and the reproducibility of 10 configurations of 4D-printed flower-shaped ceramic structures;
[0057] Fig.31 A diagram depicting a space exploration application of the SMC's 4DASM according to an embodiment of the present invention; and
[0058] Fig.32 Shown is the balance between thermal expansion and thermal contraction effects, which serves as one of the key mechanisms of 4D printing. DETAILED DESCRIPTION
[0059] In the following description, SMC, its manufacturing method and 4D printing are described as preferred examples. It will be apparent to those skilled in the art that modifications including additions and / or substitutions can be made without departing from the scope and spirit of the invention. Certain details may be omitted so as not to obscure the invention; however, this disclosure is written to enable those skilled in the art to practice the teachings herein without conducting experiments.
[0060] Color drawings are filed with the specification. Color drawings are necessary as the only practical medium by which aspects of the claimed subject matter can be accurately conveyed. Color drawings are the only practical medium by which to disclose the subject matter for which patents are sought because the claims are directed to a SMC heating process with controlled temperature where the use of different colors is the only practical way to demonstrate different temperatures on different parts or areas of the structure of the claimed subject matter.
[0061] According to one aspect of the present invention, a SMC is provided. According to another aspect of the present invention, a method for manufacturing a SMC is provided.
[0062] In one embodiment, the SMC is made from elastomer derived ceramic (EDC) and the elastomer is processed with UV / ozone treatment prior to pyrolysis.
[0063] In this embodiment, a ceramic precursor is provided prior to pyrolysis. The ceramic precursor includes polydimethylsiloxane (poly(dimethylsiloxane) or PDMS), and a UV / ozone treatment is applied to a portion of the ceramic precursor. The UV / ozone treatment is a process involving exposing the ceramic precursor to ultraviolet (UV) light in the presence of ozone gas.
[0064] After treatment, in the described embodiments, a heterogeneous ceramic precursor is provided, and the treated portion of the heterogeneous ceramic precursor has a different thermal expansion coefficient or a different thermal shrinkage rate than the remaining portion or remaining portion of the heterogeneous ceramic precursor. After pyrolysis, an SMC is provided, and the shape of the SMC can be modified during pyrolysis and subsequent heating treatment.
[0065] In some embodiments, the ceramic precursor includes polysiloxane (silicone oil), polyborosiloxane (PBS), polycarbosiloxane, polysilazane, polysilazane, poly(organosilylcarbodiimide), poly(organosilylcarbodiimide), hydrogel, or a combination thereof.
[0066] The following description refers to Figure 1-3 According to one embodiment of the present invention, the precursor structure 1A provided in this step has a plurality of grooves 10, such as Figure 1 More specifically, the precursor structure 1 of this embodiment is substantially a flat structure having two wide surfaces 11 and 12, and all the grooves 10 are formed on one of the surfaces (ie, surface 11), while the other surface (ie, surface 12) remains flat.
[0067] In this example, the precursor structure 1 is constructed with an elastomeric material comprising PDMS, and the precursor structure 1 is constructed with a unique structural design, introducing specific features in regions specifically designed for further shape modification in subsequent SMC conversion.
[0068] In this embodiment, the depth of the groove 10 is 100 micrometers. In some other embodiments, the depth of the groove 10 may be 200 micrometers or 500 micrometers. Therefore, the precursor structure 1A can be easily obtained through subtractive manufacturing such as laser engraving.
[0069] Figure 2 is another schematic diagram of the precursor structure of this embodiment. Figure 2 As shown, after providing the precursor structure 1A, the manufacturing method of this embodiment treats a portion 120 of the surface (ie, the surface 12) of the precursor structure with UV / ozone. The surface 12 of the precursor structure and the adjacent portion 120 are completely treated with UV / ozone.
[0070] In other words, in this embodiment, a thin film is formed on the surface 12 of the precursor structure 1A after the UV / ozone treatment, wherein the film thickness is adjusted by changing the treatment time in the UV / ozone system.
[0071] In this step, a precursor structure is provided that exhibits heterogeneity in thermal expansion-contraction behavior across different parts, and the heterogeneity causes shape changes in subsequent steps. In other words, a ceramic precursor that exhibits changes in thermal expansion and contraction behavior across different regions is provided in this step, and the changes cause shape changes in subsequent steps of SMC manufacturing.
[0072] More specifically, while the portion 120 of the precursor structure is treated with UV / ozone, the portion 110 of the precursor structure is shielded from the UV / ozone treatment. The portions 110 and 120 are bonded, and the portion 110 has the groove 10. The thermal expansion and contraction behavior of the portion 110 is different from the thermal expansion and contraction behavior of the portion 120.
[0073] After UV / ozone treatment, the manufacturing method of this embodiment uses pyrolysis to process the precursor structure to produce Figure 3 SMC 2A shown. UV / Ozone treatment indicates the use of UV light and ozone in a combined treatment process, with both components applied simultaneously or in a coordinated manner. Pyrolysis in this example is a chemical process in which a ceramic precursor is heated to a high temperature in the absence of oxygen or in a limited supply of oxygen, i.e., in an inert atmosphere such as argon. During pyrolysis, the polymers of the precursor structure decompose, leaving behind a ceramic residue.
[0074] In other words, the steps involve a polymer to ceramic conversion phase, thereby forming the SMC 2A. However, the present invention is not limited to the shape and curvature of the SMC 2A.
[0075] SMC2A includes a portion 20 and a portion 21. The portion 20 and the portion 21 of SMC2A are bonded, and SMC2A is an elastomer-derived ceramic including silicon oxycarbide.
[0076] In the above steps, the portion 20 of the SMC 2A is treated with UV / ozone, and the portion 21 of the SMC is not treated with UV / ozone. Thus, the pyrolysis induces a shape change and forms the SMC 2A, and 4D printing is performed.
[0077] Furthermore, the shape of the SMC 2A can be further modified by a heating process in an air atmosphere. Since the portion 20 and the portion 21 still have different thermal expansion and contraction behaviors, the shape of the SMC 2A can be further modified by performing an additional heating process in an air atmosphere.
[0078] In other words, after pyrolysis, SMC 2A is a first generation EDC with a modified shape. In order to further modify its shape, at least a portion of SMC 2A can be heated in air. During the heating process, the heated portion of SMC 2A performs a shape change, thereby producing a second generation EDC after the heating process.
[0079] In some embodiments, the manufacturing method further includes heating the entire SMC in air to modify the shape of each portion of the SMC and transform the entire SMC into a second generation EDC.
[0080] In some other embodiments, the manufacturing method further includes heating a portion of the SMC in air so as to modify the shape of only certain portions of the SMC, and those portions of the SMC are changed into the second generation EDC.
[0081] In some other embodiments, the manufacturing method further includes heating at least a portion of the SMC using a flame gun in air. The step may transform a portion of the SMC or the entire SMC into a second generation EDC to perform shape modification.
[0082] The SMC 2A is therefore ideally suited for shape modification after both additive and subtractive manufacturing.
[0083] According to one embodiment of the present invention, a 4D printing method is provided. Here, the portion 21 of the SMC 2A has a plurality of grooves. Due to the shape design of the portion 21 and the difference in thermal expansion and thermal contraction behavior, the SMC 2A bends after pyrolysis and can be bent again by a heating process.
[0084] The step of providing a precursor structure 1A includes: forming a first precursor using additive manufacturing; and cutting or engraving the first precursor using a laser to form the precursor structure.
[0085] In one embodiment, additive manufacturing includes knife coating, which involves knife coating on a substrate to evenly disperse a solution on its surface, and is a highly efficient and suitable two-dimensional additive manufacturing.
[0086] In another embodiment, additive manufacturing includes direct ink writing (DIW), which involves extruding a viscous ink or paste through a fine nozzle onto a substrate or build platform. DIW allows precise control of the deposition of materials, enabling the manufacture of complex, customized materials with customized properties.
[0087] In yet another embodiment, additive manufacturing includes material jetting, photopolymerization, powder bed fusion, or a combination thereof.
[0088] In the step of forming the first precursor, the additively manufactured material includes PDMS, which is a suitable material for a ceramic precursor.
[0089] In some embodiments, the additively manufactured material comprises: polysiloxane, polyborosiloxane, polycarbosiloxane, polysilazane, poly(organosilylcarbodiimide), hydrogel, and combinations thereof.
[0090] In the step of forming the first precursor, the material of the additive manufacturing further comprises zirconium dioxide nanoparticles. For example, the concentration of the zirconium dioxide nanoparticles in the material can be 10 weight percent. In some other embodiments, the concentration of the zirconium dioxide nanoparticles in the material is 20 weight percent. Therefore, SMC and its manufacturing method can provide a zirconium dioxide-based ceramic with high temperature stability, high mechanical strength and toughness, chemical inertness and biocompatibility. The zirconium dioxide nanoparticles are added to the liquid PDMS and mixed using a three-roller machine. The mixed material can be centrifuged after being loaded into the barrel.
[0091] In some other embodiments, the additively manufactured material further comprises aluminum oxynitride nanoparticles. For example, the concentration of aluminum oxynitride nanoparticles in the material can be 50 weight percent. Therefore, SMC and its manufacturing method can provide ceramics with enhanced hardness, transparency, thermal stability and chemical inertness.
[0092] In some other embodiments, the additively manufactured material further comprises ceramic particles or glass particles, and the precursor structure comprises ceramic particles (fillers) or glass particles (fillers). Therefore, SMC and its manufacturing method can provide ceramics with different properties.
[0093] In some other embodiments, the additively manufactured material further comprises aluminum oxide, titanium dioxide, silicon nitride, calcium oxide, silicon carbide, yttrium oxide, or aluminum nitride particles or nanoparticles.
[0094] The step of cutting or engraving the first precursor using a laser provides high-precision subtractive manufacturing. In one embodiment, a silicone-based composite precursor is developed to achieve enhanced geometric flexibility, and two-dimensional (2D) additive manufacturing or DIW such as scraping is applied to generate an elastomeric ceramic precursor. At the same time, subtractive manufacturing techniques using high-energy beams (e.g., laser beams) can improve manufacturing accuracy, thereby producing a high-precision ASM system.
[0095] In some other embodiments, the step of cutting or engraving the first precursor may be performed using an electron beam, high pressure liquid or other controlled high energy beam.
[0096] The width of the grooves 10 in the precursor structure 1A can appropriately modify the expansion and contraction of the ceramic in subsequent steps. For example, the width of the grooves 10 is 1 mm, and the depth can range from 100 microns to 500 microns. These grooves 10 can be accurately formed by subtractive manufacturing using a laser, and these grooves can accurately modify the expansion and contraction of the ceramic.
[0097] In the UV / ozone treatment step, the portion 120 is processed with UV / ozone treatment for 8 hours. Thus, the portion 120 can be properly formed. In the pyrolysis step, the precursor structure is heated to 1,300° C. in an induction heating furnace at an argon flow rate of 200 milliliters per minute for 12 minutes, and the high temperature is maintained for 10 minutes. In another step after the pyrolysis, in some embodiments, the SMC is heated to 1,300° C. in air with a tube furnace for 30 minutes to provide an SMC made of a second-generation EDC.
[0098] The following description refers to Figure 4-6 In another embodiment of the present invention, the step of UV / ozone treatment includes: masking the surface 11 of the precursor structure 1B with laser cut paper 13; and treating the masked surface 11 with UV / ozone. The laser cut paper 13 can provide high-precision masking on the surface 11 to expose the portion of the surface 11 to be treated with UV / ozone.
[0099] In this embodiment, the precursor structure 1B can be manufactured via 3D printing such as DIW, and the material includes PDMS and zirconium dioxide. For example, the concentration of zirconium dioxide can be 20 weight percent. In another example, the precursor structure 1B can be an integral blade disk, that is, a component including both the rotor disk and the blade as a single component, and Figure 4 A blade section of a blisk in pre-production is shown. Section 120 is processed by UV / ozone treatment while masking the laser cut paper 13 and the position and size of section 120 can be designed with high precision using the laser cut paper 13 .
[0100] During this UV / ozone treatment step, precise masking is required to protect certain areas of the precursor structure 1B from exposure to UV light and ozone. Laser cut paper 13 provides an effective solution as a mask. Laser cut paper 13 is created by using laser cutting technology to accurately cut complex patterns or shapes into a paper sheet layer and ensure accurate masking of specific areas on the precursor structure 1B.
[0101] For example, the precursor structure 1B is planar and intersects the ground at 57°, and is selectively exposed to UV / ozone treatment for 16 hours by masking the surface 11 with laser cut paper 13 .
[0102] Using pyrolysis treatment Figure 5 The precursor structure 1B shown in FIG. Figure 6 The SMC 2B shown. However, the present invention is not limited to the shape and curvature of the SMC 2B. The portion 20 and the portion 21 are combined, and the portion 20 is treated with UV / ozone, so that the SMC 2B can perform shape change.
[0103] More specifically, during pyrolysis, the precursor structure 1B was subjected to controlled heating to 1,000°C for 2 hours in a resistance-heated furnace, followed by vacuum cooling to ambient temperature. The heating rate was maintained at 5°C per minute, and the cooling rate was 10°C per minute.
[0104] After cooling, the first generation EDC was obtained. To obtain the second generation EDC, the precursor structure 1B was subjected to additional heating. Initially, it was heated to 1,000° C. and then further heated to 1,250° C. in an air atmosphere using a tube furnace.
[0105] In this embodiment, the SMC 2B is efficiently manufactured using 4D printing including the steps described above, and the use of laser cut paper 13 provides an easy-to-use, cost-effective and compatible method. Figure 4 The precursor structure 1B shown may be a blade portion of a pre-production blisk, and as shown in FIG. Figure 6 The SMC 2B shown may be a manufactured blade part, which is best achieved by using laser cutting paper 13 .
[0106] Overall, the use of laser-cut paper masks combined with UV / ozone treatment and pyrolysis offers several advantages, including precise masking, customizability, cost-effectiveness, ease of handling, compatibility with processing techniques, reduced residues, and large size. These advantages help improve process control, efficiency, and quality in the processing of PDMS-containing components.
[0107] In some embodiments of the present invention, all steps of the manufacturing method are performed by a single manufacturing device, which can be fully automated for resource and cost efficiency. In some other embodiments, the steps of the manufacturing method of the above-mentioned embodiments can be performed in a turntable system with multiple stations. More specifically, the stations can perform different complex processes, including additive manufacturing, subtractive manufacturing, UV / ozone treatment and / or other manufacturing technologies; and each step of the manufacturing method can be performed separately and in parallel in one of the stations. For example, one of the stations can perform additive manufacturing, and another of the stations can perform subtractive manufacturing, and yet another station can perform UV / ozone treatment, all of which are performed simultaneously, thereby achieving assembly line mass production. Therefore, the manufacturing method of an embodiment of the present invention can be used for mass production.
[0108] In some other embodiments of the present invention, the manufacturing method of SMC may further include a deposition process. The deposition process includes physical vapor deposition, chemical vapor deposition, atomic layer deposition or a combination thereof. Therefore, the SMC provided in these embodiments may further include a layer for protection or any desired function.
[0109] The SMC provided in any of the above embodiments can be applied to a deformable thermal protection system or a space folding system. In addition, the SMC can be applied to on-orbit manufacturing and repair.
[0110] The following description explains the SMC, its manufacturing and 4D printing methods according to various embodiments of the present invention in more detail from different perspectives.
[0111] According to one embodiment of the present invention, a silica-based composite precursor is developed to achieve enhanced geometric flexibility, and then scraping (two-dimensional (2D) additive manufacturing) or ink direct writing (DIW) (3D additive manufacturing) is applied to generate an elastomeric ceramic precursor. At the same time, a subtractive manufacturing technique using a high-energy beam (e.g., a laser beam) is used to improve manufacturing accuracy, resulting in a high-precision ASM system. The elastomeric ceramic precursor for 2D / 3D additive manufacturing applications is then laser engraved or cut using an optimized laser scanning strategy, which involves precise control of the laser scanning power and speed. Subsequently, the treated precursor is heat treated to transform it into a structural ceramic.
[0112] 4D printing of ceramic materials has been developed by modulating heterogeneous precursors. By integrating elastic precursor laser cutting / engraving (EPLC / EPLE) technology and ceramic 4D printing technology, the present invention has developed a 4D ASM paradigm for ceramic materials with complex shapes, high precision, low cost and environmental friendliness. This fully embodies the integration of modern advanced manufacturing technology and ancient ceramic skills.
[0113] Figure 7 Representative ceramic 4D printing strategies according to various embodiments of the present invention are shown. First, a high-precision laser is used to modulate the structural stiffness of the sample. Subsequently, a thin film is produced on the surface of the sample by a UV / ozone system, and the film thickness is modulated by changing the processing time in the UV / ozone system. The sample is then subjected to heat treatment under inert gas or vacuum conditions. The thermal expansion and thermal contraction behaviors of the UV / ozone treated material and the untreated 3D printed precursor material are different, and this heterogeneity causes shape changes in the precursor structure. In addition, due to the different thermal contraction behaviors of materials derived from UV / ozone treated precursor materials and non-UV / ozone treated precursor materials, the 4D printed first-generation EDC can be further deformed by overall or local heat treatment in air to produce a second generation or a first generation / second generation composite EDC.
[0114] By using the manufacturing method according to the embodiment of the present invention, the grooves on the precursor structure can be accurately designed. Figure 8 As shown, the precursor structures 8A-8E have a UV / ozone film located on the top, and the UV / ozone film is treated by UV / ozone treatment. A groove is formed at the bottom of each precursor structure. The depth of the groove in the precursor structure 8A is 100 microns; the depth of the groove in the precursor structure 8B is 200 microns; the depth of the groove in the precursor structure 8C is 300 microns; the depth of the groove in the precursor structure 8D is 400 microns; and the depth of the groove in the precursor structure 8E is 500 microns. These precursor structures 8A-8E are manufactured via ASM, and the materials of these precursor structures include PDMS and zirconium dioxide at a concentration of 10 weight percent. The grooves are formed via a carbon dioxide laser processing device, and the width of each groove is 1 mm.
[0115] In some embodiments, an induction heating furnace is used to achieve rapid one-step shape / material changes of precursor structures. Material and shape changes of engineered heterogeneous ceramic precursors can be achieved simultaneously in as fast as a few seconds with heating rates of 1,000 °C min-1. 1 , which is 100 times that of conventional resistance heating technology. Induction heating is an efficient, energy-saving and environmentally friendly heating method with a wide range of applications such as metal melting, surface heat treatment and sintering of ceramic composite materials. Induction heating converts electrical energy into thermal energy, and the utilization rate of electrical energy is high, the heating efficiency exceeds 90%, and the energy consumption is only 1 / 3 of conventional heating.
[0116] like Fig. 9 As shown, it shows the shape and material changes of the ceramic precursor structure with a groove depth of 100-500 microns (such as Figure 8The precursor structure was heated to 1,300° C. (wherein Fig. 9 B shows the precursor structure after 4 minutes and 33 seconds, and Fig. 9 C shows the precursor structure after 12 minutes). Subsequently, the temperature of the induction heating furnace environment was maintained at 1,300°C for 10 minutes (where Figure 8 D shows the precursor structure after 22 minutes). The result was the first generation EDC.
[0117] In some embodiments, a smooth boron nitride (BN) plate is selected as the substrate because BN is well known for its excellent thermal stability and low friction behavior. The BN substrate is also used to reduce friction and adhesion, which may cause external forces to be applied to the material during deformation.
[0118] The use of ASM in the fabrication method allows for precise groove design. Such precise groove design in turn ensures versatility in building complex structures with zero, negative, positive, and mixed Gaussian curvatures. Due to the different thermal expansion and contraction behaviors of the heterogeneous precursor structures, the ceramic precursors change in both shape and material composition when subjected to thermal treatment.
[0119] Thermogravimetric analysis and differential scanning calorimetry showed that the polymer-to-ceramic transformation was achieved at 300-900°C. 2 The Young's modulus of the elastomer and UV / ozone microfilm are 1MPa and 13MPa, respectively. The average compositions of the elastomer and UV / ozone film are SiO 1.23 C 1.45 Zr 0.05 and SiO 3.13 C 14.81 Zr 0.01 The difference between the thermal expansion behavior of the elastomer and the UV / ozone film results in bending deformation. Furthermore, the bending stiffness of the ceramic precursor and the curvature of the resulting ceramic can be precisely modulated by modifying the depth and width of the laser-engraved grooves.
[0120] Fig.10 FEA simulation showing the effect of thermal expansion on bending deformation, which is similar to Fig. 9 The image shows the shape and material changes of the ceramic precursor structure during the heating process. The precursor changes to ZrO with porous features. 2 -SiOC nanocrystalline-amorphous dual phase (NCADP) ceramics or amorphous SiOC glass. Figure 11 shows the SiOC nanocrystalline-amorphous dual phase (NCADP) ceramics or amorphous SiOC glass. Fig. 9 SEM image of the first generation EDC of the precursor subjected to induction heat treatment at 1,300°C is shown; Fig.11ADisplay the sample surface, and Fig. 11B and 11C Show the fracture surface.
[0121] Figure 12 shows the derivatives Fig. 9 The porosity of the first generation EDC of the precursor subjected to induction heat treatment at 1,300°C is shown; Fig. 12A Display ceramics N 2 The absorption / desorption isotherms and the Brunauer-Emmett-Teller specific surface area are 310 m 2 g -1 ,and Fig. 12B The cumulative pore volume and pore size distribution of the ceramics obtained using nonlinear density functional theory analysis are shown, and the cumulative pore volume (≤128 nm) is 0.308 mL g -1 .
[0122] It can be demonstrated that the 4D printed ceramic structure is capable of secondary self-deformation and reversible reconfigurability. When the ceramic is heated in air, the thermal shrinkage behavior of the first generation EDC derived from heterogeneous precursors remains heterogeneous. 2 The first generation EDC of homogeneous precursor material showed linear shrinkage of 3.5% and 5.6% when heated in air at 1,000°C and 1,200°C, respectively.
[0123] The reconfigurability of the corresponding first-generation EDC derived from a heterogeneous precursor subjected to UV / ozone treatment can be modulated by heating in air under different conditions. In general, the higher the heating temperature applied to the first-generation EDC (below the deformation endpoint), the more the produced second-generation EDC recovers to its initial shape. If the deformation endpoint is higher than the initial shape memory point, the first-generation EDC bends in the opposite direction and exhibits reverse shape memory capability. Under appropriate heating conditions, the SMC can be reversibly reconstructed into the initial planar shape of the precursor, or even the reverse curved shape of the first-generation EDC, resulting in initial / reverse multimodal shape memory behavior of the second-generation EDC and ceramics. Similarly, local heat treatment in air, such as heating in the middle or on one side, provides flexibility for local re-ceramicization and self-deformation of the first-generation EDC, thereby generating first-generation / second-generation composite EDCs with a variety of shapes.
[0124] In some embodiments of the present invention, the difference in thermal expansion coefficient of the precursor materials affects the first stage shape change before the elastomer is converted to ceramic. After the elastomer is converted to ceramic, the difference in thermal shrinkage of the precursor materials can further affect the second stage shape change with significant material change. When the first generation EDC produced is heated in air, the heterogeneity of the thermal shrinkage behavior of the first generation EDC leads to initial / reverse multi-mode shape memory behavior and re-ceramicization to the second generation EDC.
[0125] In brief, after the heating process, the precursor structure exhibits different curvatures due to the difference in groove depth, thereby providing a first generation EDC, the curvature of which is appropriately controlled by the formation of the grooves. The first generation EDC can then be transformed into a second generation EDC via a further heating process. Although engineering the expansion and contraction of materials is a common strategy for 4D printing, the present invention presents a successful attempt at ceramic 4D printing by recording the balance between thermal expansion and thermal contraction.
[0126] Figure 13-16 The foregoing embodiment is further presented. Fig.13 Depicting images of a first generation EDC derived from a precursor structure with grooves 200 microns deep at different time points and temperatures during heat treatment. As shown, the first generation EDC was heated to 1,300°C in air for 30 minutes in a tube furnace to produce a second generation EDC. Fig.14 Depicting images of a first generation EDC derived from a precursor structure with grooves having a depth of 500 micrometers at different time points and temperatures during a heating process. As shown in the figure, the first generation EDC was heated to 1,300°C in air for 30 minutes by a tube furnace to produce a second generation EDC. Fig.15 Depicting images of a first generation EDC derived from a precursor structure having grooves with a depth of 100 micrometers at different time points and temperatures during a heating process. As shown in the figure, the first generation EDC is heated to 1,300°C in air for 30 minutes by a tube furnace to provide a second generation EDC. Fig.16 Summarize the relationship between precursor groove depth and curvature of first- and second-generation EDCs.
[0127] exist Figure 13-15 The average compositions of ceramics of the first and second generation EDCs are SiO 1.65 C 1 . 93 Zr 0.07 and Sio 2.04 C o.83 Zr 0.04 And the first generation EDC and the second generation EDC have different crystal structures. Fig.17X-ray diffraction analysis showing the crystal structure of the first and second generation EDCs. As shown in the figure, monoclinic zirconium dioxide ZrO 2 , while the second generation EDC contains tetragonal zirconium dioxide Zro 2 and silicon dioxide Sio 2 .
[0128] According to one embodiment of the present invention, the first generation / second generation composite EDC may be generated via local heating in air, ie, heating only a portion of the first generation EDC in air. Fig.18 Such a manufacturing process is shown in FIG. Fig.18 As shown, a precursor structure 18A is provided, and a first generation EDC 18B is provided by heating the precursor structure 18A under an inert gas or vacuum condition.
[0129] By heating the entire first generation EDC 18B, second generation EDCs 18C, 18D having different curvatures are generated according to the heating conditions. For example, the second generation EDC 18C is formed by heating the first generation EDC 18B at a low temperature, and the second generation EDC 18D is formed by heating the first generation EDC 13B at a high temperature. The curvature of the second generation EDC 18C is different from the curvature of the second generation EDC 18C. In this way, the curvature of the SMC is appropriately designed by controlling the heating temperature.
[0130] On the other hand, by locally heating only a portion of the first generation EDC 18B, the method produces SMCs having different shapes. For example, by heating only the middle portion of each of the first generation EDCs 18B, a first generation / second generation composite EDC 18E is produced; and by heating only one side of each of the first generation EDCs 18B, a first generation / second generation composite EDC 18F is produced. The shape of the second generation composite EDC 18E is different from that of the second generation composite EDC 18F. Therefore, the shapes of the first generation / second generation composite EDCs 18E, 18F are appropriately designed.
[0131] The ceramic 4D printing method according to an embodiment of the present invention can achieve geometric flexibility and high deformation accuracy of advanced structural ceramics, and can be used in high-temperature applications such as aerospace propulsion. A derivative demonstration of the ceramic 4D printing method is shown in an exemplary application of the present invention. Figure 19-21 There are pictures and graphic descriptions.
[0132] In this application, a ceramic engine turbine disk and 12 blades are 4D printed as a single piece, and no assembly process is required. Through local UV / ozone exposure, the blades with flat surfaces are simultaneously configured to achieve torsional deformation with high repeatability, thereby producing a flower-like symmetrical structure.
[0133] like Fig. 20 As shown, a heterostructure precursor 20A is provided, and the heterostructure precursor 20A has 12 blades 20B, and each blade has a plurality of neutral parts 20C and a UV / ozone treated part 20D. The UV / ozone treated part 20D forms a plurality of strips in the neutral part 20C, wherein the width d1 is 2 mm, the width d2 is 1 mm, the width d3 is 1.1 mm, and the angle α is 55°. The angle α can range from 45° to 60°, and the widths d1, d2, and d3 can be adjusted accordingly. The material of the heterostructure precursor 20A includes 20 weight percent of PDMS and zirconium dioxide. By heating the heterostructure precursor 20A, a ceramic integral blade disk 20E (i.e., a turbine component including both a rotor disk and blades as a single component) is produced. In this way, an efficient single-piece 4D printing manufacturing method for an engine turbine disk is provided without the need for multi-component assembly.
[0134] The high repeatability of ceramic 4D printing methods allows high manufacturing accuracy for 3D configurations and 4D deformations. Fig.22A and 22B In another exemplary application of the present invention shown, this high repeatability can be demonstrated by 4D printing five blades of a fully ceramic blisk. The FEA simulation of the effect of thermal expansion on torsional deformation is consistent with the experimental results shown in FIGS.
[0135] In such Fig.26 In yet another exemplary application shown, shape memory behavior can be demonstrated with a complex all-ceramic blisk (integral blisk) structure. In this exemplary application, the twisted blades in the first generation EDC can be modulated to the initial planar shape in the second generation EDC at an initial shape memory point of 1,239°C. Fig.27A and 27B Further shown in . Fig.27A Demonstrating shape and material changes of a first-generation EDC derived from a heterostructured precursor of a 4D-printed all-ceramic blisk under heat treatment at a maximum temperature of 1,000°C in air. Fig.27B Show as Fig.27A The shape and material changes of the resulting ceramics shown under heat treatment in air at a maximum temperature of 1,250°C, resulting in a second generation EDC;
[0136] Therefore, the shape of the blade can be further adjusted by changing the first generation EDC to the second generation EDC. Fig.26 As shown, the twisted blades of the first generation EDC 26A may be changed into different shapes and the second generation EDC 26B may be provided by heat treating the first generation EDC 26A.
[0137] The industrial potential of the embodiments of the present invention can be realized by the large-scale production capability of heterogeneous precursor materials assisted by a multi-station turntable system. To increase the manufacturing speed, the scraping is performed using a face-by-face printing strategy instead of DIW in a line-by-line printing strategy. The EPLC method and UV / ozone surface treatment ensure the manufacturing accuracy of 3D configuration and 4D deformation, respectively. For example, Figures 28 to 30 As shown, the ceramic 4D printing method can prepare a 10×10 heterogeneous precursor array of ceramic kirigami structures with fine features and high repeatability within 50 minutes (within 30 seconds per sample on average). And on average, each sample has within 50 minutes or 30 seconds.
[0138] The present invention broadens the application scope of high temperature structural materials in the fields of aerospace, electronics, biomedicine and art. The 4D printing method according to the embodiment of the present invention can even be applied to space exploration, for example, Fig.31 Deformable thermal protection system shown. Specifically, 4D printed SMCs enhance the flexibility of thermal protection systems for reentry vehicles / space capsules. Using real-time measurement data, an optimized and reliable thermal protection system with deformation capabilities can be 4D printed in situ to account for shape-related uncertainties and variable thermal environments encountered by reentry vehicles / space capsules due to various factors such as ablation and complex flow effects. The resulting lightweight design is preferred over the design of traditional heavy heat shields because it can increase payload and reduce costs.
[0139] like Fig.31 As shown, the 4D printing method according to an embodiment of the present invention can be used in space for on-orbit manufacturing of ultra-high performance turbine blades or on-orbit repair (e.g., additive remanufacturing) of heat shields and other necessary components that may fail during long-term missions. Compared with traditional technologies, manufacturing and repair based on 4D printing methods are faster and cheaper, and the cost of placing ultra-large-scale components in or outside the orbit required by traditional technologies is too high.
[0140] The proposed ASM system according to an embodiment of the present invention can be used to achieve fast, precise and large-scale manufacturing of ceramic materials by increasing the 3D printing efficiency from line-by-line printing to surface-by-surface printing. The laser beam technology used in SM can be extended to other controlled high-energy beams, such as electron beams, ion beams, high-pressure liquids, and combinations of these. The framework involving UV / ozone films on elastomeric polymers can be extended to other 2DAM materials such as metal films to achieve heterogeneous precursors.
[0141] In summary, before the elastomer-to-ceramic transition, the difference in thermal expansion coefficients of the precursor materials leads to a first-stage shape change. After the elastomer-to-ceramic transition, the difference in thermal shrinkage of the precursor materials leads to a second-stage shape change with significant material changes. When the resulting first-generation EDC is heated in air, the heterogeneity of the thermal shrinkage behavior of the first-generation EDC leads to initial / reverse multimodal shape memory behavior and re-ceramicization to the second-generation EDC. Therefore, the balance between thermal expansion and thermal contraction is one of the key mechanisms of 4D printing of ceramic materials, such as Fig.32 shown.
[0142] In various embodiments of the present invention, the development of SMC begins with a martensitic phase transformation. The present invention introduces a new mechanism for manufacturing SMCs using the heterogeneity of thermal expansion-contraction behavior. Using the newly developed SMC manufacturing mechanism, a universal SiOC-based SMC can be developed in a convenient manner by physically mixing liquid silicone with different ceramic fillers. Compared with (i.e.) ceramic powder pressing used in the art, geometric flexibility is significantly enhanced by 4DASM (2D / 3D printing plus laser engraving / cutting of ceramic precursors). In addition, the size of the structural SMC is expanded from micro / mesoscopic to macroscopic scales, thereby realizing the initial / reverse and overall / local multi-mode shape memory capabilities of ceramics. Therefore, these aspects distinguish the present invention from existing manufacturing methods of SMCs. Table 1 below summarizes the distinction between the present invention and previous work on SMCs. Table 1
[0143] experiment
[0144] The embodiments of the present invention were verified in experiments, and the experimental results are presented below.
[0145] Preparation of materials:
[0146] For ceramic materials, Fig. 9 , 13 The ink used for the precursor shown in 16, 18, 20, 21, 26, 27A and 27B is composed of ZrO 2 Nanoparticles (Tong Li Tech Co., Ltd.) and poly (dimethylsiloxane) (PDMS, SE1700, Dow Corning) were used. 10 or 20 wt% ZrO 2 The nanoparticles were added to the liquid PDMS and mixed using a three-roll mill (Exakt). The ink was then poured into a cartridge and centrifuged. Fig.30The ink shown for the precursor consists of AlON nanoparticles (50 wt%) and PDMS (SE1700, Dow Corning). For SiOC glass, liquid PDMS ink (SE1700, Dow Corning) was poured into a cartridge and centrifuged.
[0147] 4D ASM:
[0148] In order to achieve the bending of heterogeneous ceramic precursors during the induction heating process, e.g. Fig. 9 As shown, a DIW machine (Regenovo Biotechnology) was used with PDMS / 10wt% ZrO 2 The solid precursor (22 mm × 2 mm × 0.8 mm) was 3D printed with the ink. The printed precursor was then cured in an oven at 150 °C for 30 min. 2 The cured precursor was laser engraved by a laser processing device (Epilog) to generate 11 evenly distributed grooves on the top surface. The width of each groove was 1 mm, and its depth was 100, 200, 300, 400 and 500 μm. The sample was then turned over and subjected to UV / ozone treatment for 8 hours. The prepared heterogeneous ceramic precursor was heated to 200 mL min within 12 minutes. -1 The sample was heated to 1,300 °C in an induction heating furnace with an argon flow rate of 1.5 % and maintained at this temperature for 10 min. In order to achieve shape memory behavior, Figure 13-16 As shown, the first generation EDCs with groove depths of 100, 200, and 500 μm derived from the ceramic precursor were then heated to 1,300° C. in air for 30 minutes using a tube furnace to produce the second generation EDCs.
[0149] In order to achieve overall shape memory behavior, such as Fig.27A and 27B As shown, a tube furnace was used to precipitate the PDMS / 10wt% ZrO 2 The first generation of EDCs were heated to 1,000°C or 1,200°C in air for 2 hours. To achieve local shape memory behavior, such as Fig.27A and 27B As shown, the PDMS / 10wt% ZrO 2 The first generation of EDC was locally heated in the middle or on one side of the sample with a flame gun in air to over 1,350°C for 10 minutes. A high temperature alloy mask with circular holes was used to perform local heat treatment on the sample.
[0150] For 4D printing and integrated molding of ceramic blisks, such as Fig. 20 and 21 As shown, PDMS / 20wt% ZrO 2The ink was used to 3D print an engine turbine disk sample (inner and outer diameters of 10 mm and 32 mm, respectively) with 12 blades (24 mm × 9 mm × 0.9 mm). The surface of each blade is planar and intersects the ground at 57°. Each blade was then selectively exposed to UV / ozone treatment for 16 h by masking the surface with laser-cut paper. The prepared heterogeneous ceramic precursor was heated to 1,000 °C for 2 h and subsequently cooled to ambient temperature under vacuum in a resistive heating furnace. The heating rate and cooling rate were 5 °C min -1 and 10℃ min -1 . Afterwards, in order to achieve shape memory behavior, e.g. Fig.26 , 27A As shown in FIG. 27B , a first generation EDC derived from a heterogeneous precursor for a 4D printed all-ceramic blisk was first heated at 1,000° C. and then at 1,250° C. in air using a tube furnace to produce a second generation EDC.
[0151] To demonstrate the mass production capability of some embodiments, a ceramic precursor film (thickness: 0.5 mm) was subjected to 2D AM using a doctor blade device. The precursor film was cured at 100°C for 30 minutes and then at 150°C for 20 minutes. The surface of the precursor film was subjected to UV / ozone treatment for 50 minutes. Subsequently, the heterogeneous precursor was laser cut into a 10×10 design structure array within 4.5 minutes. All processing steps were controlled within 50 minutes, and with the help of a multi-station turntable system, the mass production efficiency of heterogeneous precursor materials can be as high as an average of 30 seconds per product.
[0152] Characterization:
[0153] Scanning electron microscopy analysis (SEM, TescanClara, Tescan; Nova-Nono430, FEI) was used to characterize the structure of the ceramic and UV / ozone films on the surface of the ceramic precursor. In order to characterize the porous features within the EDC, a pore size analyzer (BSD-PS(M), BeiShiDe Instruments) was used to obtain the N 2Absorption-desorption isotherms. The specific surface area and pore size distribution of EDC were obtained using Brunauer-Emmett-Teller analysis and nonlinear density functional theory, respectively. A mercury intrusion porosimeter (MicroActiveAutoPoreV9600, Micromeritics Instruments) was used to measure the porosity of the printed ceramic grid. Optical profilometer measurements of large-scale paper-cut samples (NPFLEX, Bruker) were obtained to determine the 3D morphology. Optical 3D scanning (ATOS Core 200, Abad Deghat Markazi Company) was performed to quantify the repeatability of the blades of the 4D-printed all-ceramic integral blade disk. A 3D-printed solid sample (75 mm × 10 mm × 1 mm) was used at 5 mm min -1 Tensile testing of the precursor was performed (Testpilot-10, Wance) at a displacement rate of 1.5 Å. Nanoindentation testing (Hysitron TI980, Bruker) was performed on the surface of the UV / ozone film to obtain the modulus for FEA simulation. -1 Thermal expansion tests of the precursors were performed on 3D printed solid samples (20 mm × 20 mm × 4 mm) heated to 300 °C at a rate of 1 200 °C (DIL402C, NETZSCH).
[0154] simulation:
[0155] FEA was performed using the commercial software ABAQUS (2016) to verify the deformation behavior during thermal expansion. The UV / ozone membrane was modeled as an elastic shell. The precursor and UV / ozone membrane were assumed to be incompressible Neo-Hookean and elastic materials, respectively. The mechanical properties and dimensions of the structure were consistent with the experimental measurements. According to the results of the thermal expansion test, the PDMS / 10wt% ZrO 2 and PDMS / 20wt%ZrO 2 The linear thermal expansion coefficients before conversion to ceramics are 283×10 -6 and 242×10 -6 ℃ -1 According to the tensile test results, PDMS / 10wt% ZrO 2 and PDMS / 20wt%ZrO 2 The modulus of PDMS / 20wt% ZrO was set to 1.14MPa and 1.56MPa respectively. During the loading process, 0-10% strain was applied to obtain the corresponding Young's modulus. The thickness of the UV / ozone film exposed for 8 hours was set to 33 microns according to the SEM results, and its modulus was set to 13MPa according to the nanoindentation results. 2The thickness of the UV / ozone film exposed for 16 hours was set to 38 μm, and its modulus was set to 20 MPa based on the nanoindentation results. The modulus of the equivalent film was calculated by assuming the same tensile stiffness across the cross section. The thermal expansion of the precursor dominates the shape change before significant material changes. Therefore, only thermal expansion was considered in the simulation.
[0156] The functional units and modules of the manufacturing and 4D printing methods of the SMC according to the embodiments disclosed herein can be implemented using a computing device, a computer processor or an electronic circuit system, including but not limited to an application specific integrated circuit (ASIC), a field programmable gate array (FPGA), a microcontroller and other programmable logic devices configured or programmed according to the teachings of the present disclosure. The computer instructions or software codes running in the computing device, computer processor or programmable logic device can be easily made by practitioners in the field of software or electronic technology based on the teachings of the present disclosure.
[0157] All or part of the method according to the embodiment may be executed in one or more computing devices including a server computer, a personal computer, a laptop computer, a mobile computing device (eg, a smart phone), and a tablet computer.
[0158] Embodiments may include computer storage media, transient and non-transitory memory devices having stored therein computer instructions or software codes that may be used to program or configure a computing device, a computer processor, or an electronic circuit system to perform any of the processes of the present invention. Storage media, transient and non-transitory memory devices may include, but are not limited to, floppy disks, optical disks, Blu-ray disks, DVDs, CD-ROMs and magneto-optical disks, ROMs, RAMs, flash memory devices, or any type of medium or device suitable for storing instructions, codes, and / or data.
[0159] Each of the functional units and modules according to various embodiments may also be implemented in a distributed computing environment and / or a cloud computing environment, where all or part of the machine instructions are executed in a distributed manner by one or more processing devices interconnected by a communication network, such as an intranet, a wide area network (WAN), a local area network (LAN), the Internet, and other forms of data transmission media.
[0160] The foregoing description of the present invention has been provided for the purpose of illustration and description. It is not intended to be exhaustive or to limit the invention to the precise form disclosed. Many modifications and variations will be apparent to those skilled in the art.
[0161] The embodiment was chosen and described in order to best explain the principles of the invention and its practical application, thereby enabling others skilled in the art to understand the invention for various embodiments and with various modifications as are suited to the particular use contemplated.
Claims
1. A shape memory ceramic, characterized in that: include: a first portion of the shape memory ceramic; as well as a second portion of the shape memory ceramic; wherein the first portion and the second portion of the shape memory ceramic are bonded, and the shape memory ceramic is an elastomer-derived ceramic comprising silicon oxycarbide; and The first portion of the shape memory ceramic is treated with ultraviolet ozone, and the second portion of the shape memory ceramic is not treated with ultraviolet ozone.
2. The shape memory ceramic according to claim 1, characterized in that: The second portion of the shape memory ceramic has one or more grooves.
3. The shape memory ceramic according to claim 1, characterized in that: The first portion of the shape memory ceramic forms one or more strips on a surface of the second portion of the shape memory ceramic.
4. A method for manufacturing shape memory ceramics, characterized in that: include: providing a precursor structure including polydimethylsiloxane (PDMS); treating a portion of the surface of the precursor structure with ultraviolet ozone; as well as The precursor structure is treated using pyrolysis to produce the shape memory ceramic.
5. The manufacturing method according to claim 4, characterized in that: The step of providing the precursor structure comprises: forming a first precursor using additive manufacturing; and The first precursor is cut, engraved or polished using a laser or a mechanical tool to form the precursor structure.
6. The manufacturing method according to claim 5, characterized in that: The additive manufacturing comprises one or more printing techniques; and The printing techniques include direct ink printing and scraping.
7. The manufacturing method according to claim 4, characterized in that: The step of treating with ultraviolet ozone comprises: masking a surface of the precursor structure; and Treat the masked surface with UV ozone.
8. The manufacturing method according to claim 4, characterized in that: After the pyrolysis treatment, the method further comprises: The shape memory ceramic is heated in air.
9. The manufacturing method according to claim 4, characterized in that: After the pyrolysis treatment, the method further comprises: A portion of the shape memory ceramic is heated in air.
10. The manufacturing method according to claim 4, characterized in that: After the pyrolysis treatment, the method further comprises: At least a portion of the shape memory ceramic is heated in air using a flame gun.
11. The manufacturing method according to claim 4, characterized in that: The steps are performed in a turret system having a plurality of stations, and each step is performed individually and in parallel in one of the stations to achieve large-scale production of shape memory ceramics.
12. The manufacturing method according to claim 4, characterized in that: The precursor structure further comprises a ceramic filler or a glass filler.
13. A four-dimensional (4D) printing method for shape memory ceramics, characterized in that: The method comprises: Two-dimensional / three-dimensional (2D / 3D) printing of structures of materials including inks and precursors; treating the structure with ultraviolet ozone to produce a heterogeneous precursor, wherein the treated portion of the heterogeneous precursor has a different coefficient of thermal expansion or a different thermal shrinkage than a remaining portion of the heterogeneous precursor; heating the heterogeneous precursor, wherein a difference in the coefficient of thermal expansion or the rate of thermal contraction between the treated portion of the heterogeneous precursor and the remaining portion of the heterogeneous precursor induces interfacial stresses to cause a selected degree of deformation to produce a first generation ceramic; and The first generation ceramic is heated, wherein the heterogeneity of thermal contraction or thermal expansion behavior of the first generation ceramic results in initial / reverse multi-modal shape memory behavior and re-ceramicization into a second generation ceramic.
14. The method according to claim 13, characterized in that The first generation ceramic can be reversibly reconfigured to the original shape of the heterogeneous precursor under appropriate heating conditions, thereby producing a second generation ceramic with initial shape memory behavior.
15. The method according to claim 14, characterized in that The second generation ceramic with the initial shape memory behavior is further deformed in the opposite direction into the reverse deformed shape of the first generation ceramic under appropriate heating conditions, thereby producing the second generation ceramic with reverse shape memory behavior.
16. The method according to claim 13, characterized in that The heating of the first generation ceramic is localized and provides flexibility for localized re-ceramicization and self-deformation of the first generation ceramic, thereby producing first generation / second generation composite ceramics having a variety of shapes.
17. The method according to claim 13, characterized in that The treating the structure with ultraviolet ozone to generate a heterogeneous precursor is a whole treatment of the structure or a local treatment of the structure assisted by a mask.
18. The method according to claim 13, characterized in that Further comprising removing a portion of the structure before or after treating the structure with ultraviolet ozone to produce a structure with a certain shape.
19. The method according to claim 13, characterized in that The heating is performed by induction heating, resistance heating or a combination thereof.
20. The method according to claim 19, characterized in that The heating is performed under an inert gas or vacuum condition to obtain the first generation ceramic, and is performed in air to obtain the second generation ceramic.
21. The method according to claim 18, characterized in that The removing of a portion of the structure is performed by a controlled laser beam.
22. The method according to claim 18, characterized in that The removing of a portion of the structure is performed by carving, cutting, polishing or a combination thereof.
23. The method according to claim 18, characterized in that The removing of a portion of the structure is performed by electron beam, high pressure liquid or other controlled high energy beam, or a combination thereof.
24. The method according to claim 13, characterized in that Further included is the use of doctor blade coating, laser cutting, or a combination thereof to perform large-scale and rapid production of heterogeneous precursor materials.
25. The method according to claim 24, characterized in that The implementation of large-scale and rapid production of heterogeneous precursor materials is aided by a multi-station turret system.
26. The method according to claim 13, characterized in that The ink comprises a polymer, or a mixture of a polymer and particles; and The particles are selected from one or more of ceramic particles and glass particles.
27. The method according to claim 13, characterized in that The precursor is selected from poly(dimethylsiloxane), polysiloxane, polyborosiloxane, polycarbosiloxane, polysilazane or poly(organosilylcarbodiimide), hydrogel or a combination thereof.
28. The method according to claim 26, characterized in that The ceramic particles are selected from one or more of the following: zirconium oxide (ZrO2), aluminum oxynitride (AlON), aluminum oxide (A12O3), titanium dioxide (TiO2), silicon nitride (Si3N4), calcium oxide (CaO), silicon carbide (SiC), yttrium oxide (Y2O3) or aluminum nitride (AlN) particles.
29. The method according to claim 13, characterized in that The size of shape memory ceramics is of macroscopic scale for engineering applications.
30. The method according to claim 13, characterized in that The 2D / 3D printing is selected from material extrusion (ink direct writing printing), doctor blade coating, material jetting, photopolymerization, powder bed fusion or a combination thereof.
31. The method according to claim 13, characterized in that Further including physical vapor deposition, chemical vapor deposition, atomic layer deposition or a combination thereof.
32. A shape memory ceramic for a deformable thermal protection system or a space origami system, characterized in that: The shape memory ceramic is 4D printed by the method according to claim 13.
33. A method for on-orbit manufacturing and repair, characterized in that: A 4D printing method comprising the shape memory ceramic according to claim 13.
Citation Information
Cited By
Adjusting method of photocuring 4D printing symmetrical form surface array structure for directional transportation of liquid in any one-dimensional direction
CN121179736A